2017
DOI: 10.1515/jbcpp-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological parameters and pollutants on asthma exacerbation in Bangalore, India – an ecological retrospective time-series study

Abstract: In Bangalore city, levels of NO2 and particulate matter, temperature, rainfall, and season increase asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As shown in Tables 3 and 4, 31% (5/16) of the studies found that temperature was the only factor associated with asthma hospitalization or EDVs [4, 9, 11, 15, 18, 25]. Nearly 37% (6/16) of the studies found that both temperature and relative humidity were associated with HAs (Table 4) [6, 9, 16, 18, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Tables 3 and 4, 31% (5/16) of the studies found that temperature was the only factor associated with asthma hospitalization or EDVs [4, 9, 11, 15, 18, 25]. Nearly 37% (6/16) of the studies found that both temperature and relative humidity were associated with HAs (Table 4) [6, 9, 16, 18, 21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…The particle sizes indoor were smaller than those in ambient air in the heating season and vice versa in non-heating season [33]. Third, although the cold temperature can stress the body and result in symptom exacerbation, whereas hot temperature is associated with higher asthma prevalence, due to increased exposure to other relevant factors such as allergens [34], rainfall or humidity [35, 36] .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Furthermore, evidence shows that burden of noncommunicable diseases are increasing in India, and their risk factors have notably high prevalence even among adolescents, although our review revealed that information related to adolescent health in general and with particular emphasis on impact of air pollution in India is in scarce, there is large number of studies in India that investigated the effect of air pollution on various groups of population. (2,4,31,32,33,34,35,36,37,38,39,40) Moreover, that there are recent attempts in examining health effects of air pollution in different age groups in India, including adolescents in a cohort study design. 41 On the other hand, urbanization is happening in fast speed in developing countries with many of cities located in Asian countries with high number of population and low per capita income; consequently, population of these cities affected by air pollution along with other social and environment risk factors.…”
Section: Discussionmentioning
confidence: 99%